Pengaruh Penggunaan Bengkung (STAGEN) Terhadap Nyeri Punggung Pada ibu NIfas Di Wilayah Kerja Poskesdes Pemtang Gadung Mersam - Liza; Dewi Junita; Embun Nadia (STIKes Budi Mulia Sriwijaya, 2025)
ABSTACK Background: The postpartum period (puerperium) begins after the placenta is delivered and ends when the reproductive organs return to their pre-pregnancy state. The postpartum period lasts approximately 6 weeks, however, all genitalia will only return to their pre-pregnancy state within 3 months. Objective: To determine the effect of using a Bengkung (Stagen) on back pain in postpartum mothers. Method: This research is a quantitative research with Quasi experiment. The population in this study were all postpartum mothers in the working area of ​​Pematang Gadung Mersam Village Health Post, totaling 74 people with a sample of 17 people. Data collection was taken by measuring back pain in postpartum mothers before using bengkung on the 2nd day and after using bengkung on the 5th day using a questionnaire, then the data were analyzed univariately and bivariately. The research was conducted in the working area of ​​Pematang Gadung Mersam Village Health Post in February 2025.Results : showed a moderate pain scale (47.1%) before (Day 2) and a mild pain scale (47.1%) after (Day 5) the use of bengkung in postpartum mothers. There was an effect of the use of bengkung (stagen) on back pain in postpartum mothers in the work area of ​​the Pematang Gadung Mersam Village Health Post in 2025 with a p value of 0.000 (<0.05). Suggestion: Therefore, it is necessary to improve and make the use of bengkung as a culture in the community and it is necessary to carry out education with policy holders and health technical implementers. It is better to carry out education for the community about the use of bengkung during the postpartum period because the use of bengkung will be beneficial if used with the correct and safe procedures, and can cause discomfort during the postpartum period if used with inappropriate methods.